THE IMPORTANCE OF QUALITY IN CUSTOMER SERVICE ON THE EXAMPLE OF THE BANKING SECTOR - Katarzyna Samek (Institute of Economic Research (IER), 2017)
Competitive counts the provider that rendered by the customer service better than the other and through the quality strategy overcomes the competitors and reaches a commercial success. In view of the particular attention should be paid to the quality of the service which significantly affect the customer loyalty. The aim of this study was to investigate the importance of quality in customer service individual commercial banks. For this purpose a SERVQUAL using the questionnaire especially by which was calculated difference between expectations and insight from the consumers on the areas being audited quality customer service. Research background: Cooperative Bank in Kalisz Pomorski (Pomeranian province), Bank of Environmental Protection in Bydgoszcz (Kujawsko - Pomorskie), and a third bank, who reserved to publish their data in research. Purpose of the article: The aim of this study was to investigate the importance of quality in customer service individual commercial banks. Methodology/methods: The method used in the work to analyze the results of the survey method was SERVQL. Findings & Value added: Each subject area of service quality in the assessment of customers' needs some improvements, because in each of them there is a discrepancy between expectations and insights. Banks as service companies must be aware that the quality of service, appropriate communication with the client, contributes not only to improve their image, but primarily becomes a factor distinguishing them from competitors.
Keywords: A11; A14; B16; 330; quality; customer service; bank